miR-26a Reverses Multidrug Resistance in Osteosarcoma by Targeting MCL1 - Li, Ming; Ma, Wei (Frontiers in Cell and Developmental Biology, 2021)
The multidrug resistance (MDR) acquired in human osteosarcoma is a huge obstacle for effective chemotherapy. Recently, microRNA-26a (miR-26a) has been associated with the pathogenesis and progression of osteosarcoma, however, whether it regulates MDR in osteosarcoma is unknown. We show here that miR-26a expression declines in chemoresistant osteosarcoma after neoadjuvant chemotherapy, and its expression correlates with clinical outcome. In addition, compared with sensitive parental cells, miR-26a expression also declines in osteosarcoma MDR cells, together suggesting a negative correlation between miR-26a expression and MDR development in osteosarcoma. We also show that the enforced expression of miR-26a reverses MDR in osteosarcoma cells, and conversely, miR-26a knockdown confers MDR in chemosensitive osteosarcoma cells treated with doxorubicin, methotrexate or cisplatin. Mechanistically, miR-26a directly targets the pro-survival protein myeloid cell leukemia 1 (MCL1), and in turn, the enforced expression of MCL1 markedly antagonizes miR-26a-decreased MDR in osteosarcoma MDR cells, therefore demonstrating that miR-26a reverses MDR in osteosarcoma by targeting MCL1. Lastly, miR-26a reverses resistance to doxorubicin in osteosarcoma MDR cells xenografted in nude mice. Collectively, these results reveal a negative role and the underlying mechanism of miR-26a in the regulation of MDR in human osteosarcoma, implying a potential tactic of manipulating miR-26a for overcoming MDR in osteosarcoma chemotherapy.